2013
DOI: 10.1016/j.jped.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Oral breathing and speech disorders in children

Abstract: Mouth breathing can affect speech development, socialization, and school performance. Early detection of mouth breathing is essential to prevent and minimize its negative effects on the overall development of individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 18 publications
2
35
0
15
Order By: Relevance
“…The literature reports a relationship between abnormal breathing mode and the presence of speech disorders 18,28 . A study showed that 31.2% of mouth breathers have speech disorders, but the significance of that finding was not ascertained 29 . Another study found that mouth breathing is a risk factor for lisp in speech 30 .…”
Section: Discussionmentioning
confidence: 98%
“…The literature reports a relationship between abnormal breathing mode and the presence of speech disorders 18,28 . A study showed that 31.2% of mouth breathers have speech disorders, but the significance of that finding was not ascertained 29 . Another study found that mouth breathing is a risk factor for lisp in speech 30 .…”
Section: Discussionmentioning
confidence: 98%
“…The breath, physiological, vital and innate function of the human being, protects the upper airway and allows the satisfactory development of the craniofacial complex if performed correctly [1][2][3][4] . For proper nasal breathing, lip sealing is indispensable for generating a differentiation system of intra and extra-oral pressures in the so-called Oronasopharyngeal Space.…”
Section: Introductionmentioning
confidence: 99%
“…Hitos et al concluded that mouth breathing can affect speech development. 22 Zadurska et al also established a correlation between mouth breathing and speech sound disorders. 11 However, the percentage of mouth breathing children with speech sound disorders was lower (59%) in the quoted studies than in the present study (82%).…”
Section: Discussionmentioning
confidence: 96%